Zircon U-Pb isotopic age of Ye Yen Sun granite complex in Phan Si Pan uplift and relationship to the Red River Shear zone - Hòa, Trần Trọng; Dung, Phạm Thị; Anh, Trần Tuấn; Ying Lan, Ching-; Usuki, Tadashi; Hiếu, Trần Văn; Ly, Vũ Hoàng (Vietnam Journal of Earth Sciences, 2013)
Zircon U-Pb isotopic age data acquired from an LA-ICP-MS for five samples of granite, porphyre granite collected from four sections in the Phan Si Pan uplift area: Sa Pa-Bình Lư, Tung Qua Lìn-Sì Lờ Lầu, Nậm Xe-Sìn Suối Hồ, Trung Lèng Hồ-Pờ Hồ. The yielded results are respectively 31.25 ±0.43 Ma (LTH 21B sample-light granite undeformation), 32.94 ±0.79 Ma (LTH 20A sample-porphyre granite), 34.2±1.2 Ma (PSP 40A sample- biotite granite), 34.55±0.56 Ma (PSP 55 sample-biotite granite porphyry) and 35.39±0.44 Ma (PSP 60 sample- biotite granite of small grained size, light colored). These ages suggest that Ye Yen Sun granite is late Eocene - early Oligocen coinciding with age of initiation of left-lateral strike-slip motion along the Red River shear zone. Besides, by analyzing internal texture and comparing Th/U ratios of zircons at different age intervals it is revealed that the core of all the zircon crystals show two age ranges of, respectively, 750-800 Ma and 201-253 Ma, probably corresponding to the age of Po Sen calc-alkaline granite complex (750.1 ± 7 Ma) and Phan Si Pan biotite-hornblende granite (250Ma).